2009
DOI: 10.1111/j.1523-1739.2009.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for Improving the Scientific Foundation of Conservation Policy in North America

Abstract: The Society for Conservation Biology (SCB) can enhance conservation of biodiversity in North America by increasing its engagement in public policy. Toward this end, the North America Section of SCB is establishing partnerships with other professional organizations in order to speak more powerfully to decision makers and taking other actions--such as increasing interaction with chapters--geared to engage members more substantively in science-policy issues. Additionally, the section is developing a North America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This optimism extends to the suggestion by TEEB that even incomplete valuation not covering the full range of ecosystem services can provide useful information for decision makers, when compared with the benefits from conversion (see also Balmford et al 2002;Cimon-Morin et al 2013). Noss et al (2009) argue that even partial quantification of ecosystem service benefits is often enough to make the case for conservation, promoting conservation over conversion. A case study by Tallis and Polasky (2009) supports this idea:…”
Section: Introductionmentioning
confidence: 92%
“…This optimism extends to the suggestion by TEEB that even incomplete valuation not covering the full range of ecosystem services can provide useful information for decision makers, when compared with the benefits from conversion (see also Balmford et al 2002;Cimon-Morin et al 2013). Noss et al (2009) argue that even partial quantification of ecosystem service benefits is often enough to make the case for conservation, promoting conservation over conversion. A case study by Tallis and Polasky (2009) supports this idea:…”
Section: Introductionmentioning
confidence: 92%
“…Some of the common challenges to achieving the goals of SPIs included the identification of relevant research topics Vohland et al 2011;Sarkki et al 2013) as well as a lack of clarity about what these goals and objectives should be (Chapple et al 2011;Kim et al 2016). The most common possible solutions identified for overcoming these common challenges included joint formulation of research that would produce science to inform policy, by scientists and policymakers (Noss et al 2009;Pullin et al 2009;Ferreira et al 2012;Sarkki et al 2013;Young et al 2014;Chaves et al 2015;Nesshöver et al 2016), and developing and adjusting clear goals and priorities of SPIs among different stakeholders at the initial stage of the SPI formulation (Kim et al 2016). In a survey of the scientific community on the need and possible options for a science-policy platform, many respondents considered decision-making (i.e., policymaking) to be complex, iterative, and often selective in the information used.…”
Section: Spi Goalmentioning
confidence: 99%
“…Recently, Noss et al (2009) reported that 28.6% of the vascular plant species in United States are critically imperiled, imperiled, or vulnerable species, collectively referred to as "threatened species." According to the most recent report of the IUCN (2010a), among 7,000 plant species examined, 22% are under threat, and 33% could not be evaluated due to a lack of information.…”
Section: Figmentioning
confidence: 99%